The Effect of Profitability, Leverage and Company Size on Tax Avoidance in the Automotive Sector Manufacturing Companies - Amelia Oktrivina Siregar (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
The purpose of this research is to examine the effect of profitability, leverage and company size on tax avoidance in the automotive sector manufacturing companies in the 2012-2019 period. The sample in this study consisted of four companies that entered consistently during the research year. The period used in this research is eight years, from 2012 until 2019. The analysis data technique is panel data regression. The method used is purposive sampling method. The results of this research indicate that partially the profitability variable has a negative effect on tax avoidance. Leverage has a positive effect on tax avoidance. Company size has no effect on tax avoidance. While simultaneous testing shows that the variable profitability, leverage and company size affect tax avoidance.